Knowledge, Attitudes and Practices of Mothers on Management of Childhood Diarrhoea Among Children Under Five Years in Al Mukalla City/ Yemen- 2022 - Maysa Saeed Al Noban, Mustafa Khidir Elnimeiri, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Good knowledge, attitude and practices of caregivers is pivotal to protection, prevention and treatment of childhood diarrhoea, hence reduce mortality thereof. Objective: Our aim in this study was to determine the level of knowledge, attitudes and practices of mothers on management of childhood diarrhoea among children less than 5 years in Al Mukalla City/ Hadhramout- Yemen. Methods: Al Mukalla, Hadhramout Governorate/Yemen is the site of a cross-sectional study that was done with the help of the local population in both urban and rural settings. The 581 women whose children were younger than 5 years old were chosen at random. Information was gathered through the use of a standardised questionnaire. SPSS Statistical Package was used for the data analysis. Results: Among 581 mothers, 58% of urban mothers knew about the meaning of diarrhoea and 66.7% of rural mothers knew that continuous vomiting is one symptoms of diarrhoea. There was 68.7% of mothers did not agree that immunization can prevent diarrhoea and given ORS during repeating vomiting or diarrhoea episode (86.8%). Around 88% of mothers continued to breastfeed their children during the diarrhoea. Mothers in urban (AOR 1.008; 95% CI 0.901- 3.104) and rural (AOR 1.906; 95% CI 0.995- 9.025) at age 30-39 years old were more likely to know about diarrhoea than mothers at age >40 years. The age had significant influence in increasing the knowledge about diarrhoea (urban p= 0.001, rural p= 0.001), while mothers with good and fair knowledge were more likely to have good practice of diarrhoea than poor knowledge in both areas. Conclusion: Mother’s knowledge and practice about diarrhoea and its management with ORS was poor among the rural areas, related on their knowledge pertaining to vital issues as danger signs of dehydration, enhanced maternal knowledge would have a positive effect on their treatment of diarrhoea in children. Keywords: Diarrhoea, ORS, Knowledge, attitude, and practice.